The Gagging of God Christianity Confronts Pluralism - Carson, D. A. (Grand Rapids Zondervan Publishing House, 1996)
After an initial survey of pluralism, The Gagging of God divides into four parts: Part 1 looks at the history behind modern pluralism, especially the revolution in hermeneutics, literary theory, and epistemology; part 2 addresses religious pluralism, nota
Keywords: Theology -- Methodology. Theology, Doctrinal -- History -- 20th century. Religious pluralism